Repetition Style In The Story Of The Prophet Musa A.S. in Balaghah Science Perspective - Hami, Widodo; Mahmasoni, Muhammad Subhi (Tasamuh: Jurnal Studi Islam, 2022)
Repetition style (uslub tikrar) in the Qur'an has become something that is commonly used when viewed from the point of view of Balaghah science. Tikrar is a style of language in which the meaning to be conveyed can be more perfect and enter the mind and feelings of the reader. Although in the Arabic language and literary tradition there is a phenomenon of bad tikrar types, of course there will never be any defects or disgrace in the language style of the Qur'an. On the other hand, the Qur'an is not poetry and of course for a Muslim is a miracle. The tikar in the story of the prophet Moses has an extraordinary miraculous dimension. The structure of words or sentences in the story of the prophet Musa, although there are many repetitions, turns out to have a beautiful aesthetic that touches the heart for readers who live it seriously and deeply. The dimension of meaning in the story of the story of the prophet Musa also has a very broad meaning, not just an ordinary repetition. The dimensions of the structure of the beautiful wording and the very broad and deep meaning in the story of the story of the prophet Moses are one of the characteristics of the miracles of the Qur'an that are difficult for anyone to match. This research is library research, using the method of documentation. Primary data were taken from books, commentaries and other scientific works on style of al-Qur'an and also the style of repetition in the Qur'an. The primary data was then analyzed descriptively using the style al-Qur'an approach. Keywords: uslub, tikrar, the story of Prophet Musa